2015
DOI: 10.1371/journal.pone.0143591
|View full text |Cite
|
Sign up to set email alerts
|

SOX18 Is a Novel Target Gene of Hedgehog Signaling in Cervical Carcinoma Cell Lines

Abstract: Although there is much evidence showing functional relationship between Hedgehog pathway, in particular Sonic hedgehog, and SOX transcription factors during embryonic development, scarce data are available regarding their crosstalk in cancer cells. SOX18 protein plays an important role in promoting tumor angiogenesis and therefore emerged as a promising potential target in antiangiogenic tumor therapy. Recently it became evident that expression of SOX18 gene in tumors is not restricted to endothelium of accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…SOX17 has been reported to be down‐regulated in CRC and HCC and to suppress tumor progression by antagonizing the Wnt/β‐catenin pathway . SOX18, however, functions as an oncogene by promoting cell proliferation and by facilitating tumor metastasis in breast cancer and cervical carcinoma . Although a previous study has reported that SOX18 promotes cell proliferation and inhibits apoptosis in HCC, the mechanism underlying the oncogenic function remains largely unknown.…”
mentioning
confidence: 99%
“…SOX17 has been reported to be down‐regulated in CRC and HCC and to suppress tumor progression by antagonizing the Wnt/β‐catenin pathway . SOX18, however, functions as an oncogene by promoting cell proliferation and by facilitating tumor metastasis in breast cancer and cervical carcinoma . Although a previous study has reported that SOX18 promotes cell proliferation and inhibits apoptosis in HCC, the mechanism underlying the oncogenic function remains largely unknown.…”
mentioning
confidence: 99%
“…Consistent with an oncogenic role, some studies found that transduction of CC cell lines with SOX2 , SOX4 , and SOX18 promoted cell proliferation, metastasis, and invasion 52,66-68 . Specifically, endogenous overexpression of SOX2 or SOX4 in CC cell lines drove the cell cycle from G0/G1 to S stage by promoting expression of cell cycle promoters, such as cyclinE2, minichromosome maintenance protein 10 (MCM10), and weel protein kinase 52,66 .…”
Section: Sox Genes In Gcsmentioning
confidence: 75%
“…However, the action of SOX2 at the cellular level did not necessarily reflect the same behavior in clinical samples because of the absence of the body’s internal environment. SOX18 promoted the development of CC without clear mechanisms, so further studies are needed to clarify the mechanisms responsible for the oncogenic role of SOX18 68 . …”
Section: Sox Genes In Gcsmentioning
confidence: 99%
“…It was proved that the inhibitors GL1 and GL2, involved in the regulation of the aforementioned pathway, are also responsible for the reduction of the expression level of the SOX18 gene. Moreover, the in vitro tests on the human cervix cancer cell lines HeLa, SiHa and CaSki showed that a SOX18 overexpression did not increase the proliferative potential, but significantly increased the invasiveness and migration of the cells of this cancer (41). This could suggest a contribution of the SOX18 protein to the promotion of tumor progression in cervix cancers.…”
Section: Ovarian and Cervical Cancermentioning
confidence: 96%
“…Due to the fact that SOX18 is expressed not only by vascular endothelial cells but also by tumor cells themselves, Petrovic et al decided to investigate the role of this transcription factor in cervix cancers (41). So far, the involvement of the SOX18 protein has been confirmed in the Hedgehog pathway in non-cancerous human cells, primarily during embryonic development.…”
Section: Ovarian and Cervical Cancermentioning
confidence: 99%